Understanding of Polydopamine Encapsulation of Hydrophobic Curcumin for Pleiotropic Drug Nanoformulation. (18th November 2022) - Liu, Jie; Li, Li; Xu, Zhi Ping
Abstract: Pleiotropic drug nanoformulation promises the enhanced efficacy of nanomedicines on the market. In this study, it is demonstrated that polydopamine (PDA)‐based drug encapsulation is a potential strategy for such nanoformulation, yet its mechanism remains poorly investigated. This study elucidates the mechanism of PDA‐encapsulated Curnanoformulations (CP NPs) using hydrophobic curcumin (Cur) as a model drug via local dopamine (DA) polymerization on self‐assembled Cur NPs. The formation of PDA‐based drug nanoformulations with the core–shell structure is comprehensively investigated by controlling the key synthetic parameters, deepening the understanding of DA polymerization in the context of drugs. An intriguing morphology evolution is proposed to be the key event in the formation of CP NPs, attributing to the Cur diffusion from the core to the shell of CP NPs. Moreover, the morphological data can be used to guide the optimization of the PDA‐based nanoformulation. In addition, the verification of soluble DA polymers in CP NPs hints at the heterogeneous nature of the excipient (i.e., PDA) of CP NPs, providing a cautionary view on the long‐term safety of PDA‐formulated drugs. In sum, this study would enable the pharmaceutical development of PDA‐encapsulated Cur nanomedicines and generalize the PDA‐based nanoformulation approach for a wider range of hydrophobic drugs. Abstract : Pleiotropic drug nanoformulation can be realized by polydopamine (PDA)‐based encapsulation. The PDA‐encapsulated nanosystem features a dynamic structure driven by drug diffusion within the PDA matrix and a pleiotropic protective shell against reactive species, heating, and light irradiation. The advances in understanding the as‐developed PDA‐based nanoformulation approach would empower the development of next‐generation nanomedicines.